Masalah Aliran Maksimum dalam Sebaran Jaringan Rute Trans Jogja dari Halte Rumah Sakit Bathesda ke Halte Malioboro 1 - Deddy Rahmadi; Hakim Adidarma; Erika Putri; Ni'ma Ajrul Amilin; Dela Nuraini Safinka (Program Studi Matematika, Universitas Timor, 2025)
Yogyakarta is one of the cities with a fairly high level of transportation use. Transportation itself is one of the most important things in daily life. This study was conducted to identify the maximum flow based on graphs from the available data with several important stages in its completion. The research data used was in the form of the number of currents and capacities of the distribution of the trans Jogja network which had a route where the starting point was at the Bathesda hospital stop and the end point was located at the Malioboro one bus stop .